The Debate on the Orientation of Higher Education: the Historical Evolution of General Education and Professional Education - Yang, Jiaqi (Journal of Educational Research and Policies, 2025)
This paper aims to explore the historical evolution of general education and professional education and the dispute over their orientation in the modern education system. It reviews the origin and development of general education and professional education, points out the educational goals and social functions of the two in different historical periods, and analyzes the necessity of interdisciplinary talent training and its impact on the traditional education model in the context of the knowledge economy. The article further discusses how higher education can balance the breadth of general education and the depth of professional education in the era of globalization and informatization, and how to build an education system that adapts to the needs of future society. Higher education institutions should attach importance to interdisciplinary curriculum design and promote the cultivation of students' critical thinking and innovation capabilities in order to cope with the transformation and change of the knowledge production model. Through an in-depth analysis of history and current situation, this paper provides a new perspective and thinking on the development direction of higher education.